2019
DOI: 10.1155/2019/7431652
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Provides Hepatoprotection against Amoebic Liver Abscess Induced by Entamoeba histolytica in Hamster: Involvement of Nrf2/HO-1 and NF-κB/IL-1β Signaling Pathways

Abstract: Amoebic liver abscess (ALA) is the most common extraintestinal amoebiasis caused by Entamoeba histolytica (E. histolytica). However, despite current knowledge and scientific advances about this infection, there are no effective treatments to prevent it. Herein, the antiamoebic capacity of curcumin in a hamster model was evaluated. Curcumin (150 mg/kg, p.o., daily during 10 days before infection) considerably prevents liver damage induced at 12 and 48 h post-intrahepatic inoculation of trophozoites and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…ROS which could be augmented by hyperglycemia activate proinflammatory pathways including IKKβ and JNK which subsequently phosphorylate inhibitory sites such as Ser 307 of IRS-1 ( Ozes et al, 2001 ; Gao et al, 2002 ; Bloch-Damti and Bashan, 2005 ; Kamata et al, 2005 ). Moreover, IKKβ acts as the upstream signaling of NF-κB which stimulates the production of proinflammatory cytokines including TNF-α, IL-1β, and IL-6 which in turn further activate IKKβ and JNK ( Ajuwon and Spurlock, 2005 ; Olefsky and Glass, 2010 ; Solinas and Karin, 2010 ; Macías-Pérez and Aldaba-Muruato, 2019 ). Accordingly, ways that are able to scavenge ROS or inhibit inflammation have the potential to protect against endothelial IR and endothelial dysfunction caused by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…ROS which could be augmented by hyperglycemia activate proinflammatory pathways including IKKβ and JNK which subsequently phosphorylate inhibitory sites such as Ser 307 of IRS-1 ( Ozes et al, 2001 ; Gao et al, 2002 ; Bloch-Damti and Bashan, 2005 ; Kamata et al, 2005 ). Moreover, IKKβ acts as the upstream signaling of NF-κB which stimulates the production of proinflammatory cytokines including TNF-α, IL-1β, and IL-6 which in turn further activate IKKβ and JNK ( Ajuwon and Spurlock, 2005 ; Olefsky and Glass, 2010 ; Solinas and Karin, 2010 ; Macías-Pérez and Aldaba-Muruato, 2019 ). Accordingly, ways that are able to scavenge ROS or inhibit inflammation have the potential to protect against endothelial IR and endothelial dysfunction caused by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a potent pro-inflammatory cytokine that plays an important role in inflammation and the host defense against tissue damage; although it is produced and released in various cell types, it is produced by monocytes and macrophages, which are cells that initiate the immune response (Lopez-Castejon and Brough, 2011). Macías-Pérez et al (2019) demonstrated thatIL-1β significantly increased in hamsters with amoebic hepatic abscess and decreased after the treatment. Similarly in our study, serum IL-1β concentration in the calves with diarrhea caused by amoebiasis (56.61±6.34 ng/ml) was higher (p<0.05) than in the control group (25.15±2.12 ng/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Macroscopic and microscopic evaluations in animal models have shown that this substance can decrease ALT, ALP, and γ-GTP activities. Curcumin could also ameliorate the amoebic damage-induced reduction in glycogen content and suppress NF-κB activity and IL-1β levels while inducing a tendency toward up-regulation of Nrf2 production [ 12 ]. Moreover, curcumin could attenuate ethanol-induced hepatic steatosis via modulation of the Nrf2/FXR axis [ 13 ].…”
Section: Digestive System Diseasesmentioning
confidence: 99%